Acute Recurrent Exacerbations of Mesenteric Panniculitis With Immunosuppressive Therapy: A Case Report and a Brief Review - Dahiya, Dushyant Singh (J Investig Med High Impact Case Rep, 2020)
Mesenteric panniculitis (MP) is a rare, benign, and idiopathic disorder characterized by chronic inflammation of the mesenteric adipose tissue of the small intestine. The exact etiology of MP is unknown and its associations with underlying malignancies continues to be poorly understood. In this case report, we describe a rare case of acute exacerbations of MP in a middle-age female with a known past medical history of non-Hodgkin’s lymphoma in remission and small bowel resection for a localized carcinoid tumor. The patient was diagnosed with MP 4 years ago and started on tamoxifen therapy with adequate control of her symptoms. Last year, she reported to the emergency department with multiple episodes of sudden-onset, severe, and localized right upper quadrant abdominal pain and nausea without vomiting. She was diagnosed with an acute exacerbation of MP and a decision was made to add 60 mg prednisone daily in addition to her tamoxifen regimen. She remained symptomatically stable for the next 6 months after the start of dual therapy with tamoxifen and prednisone. However, for the past 6 months, the patient reported to the emergency department on an average of 2 times/month with the same recurrent symptoms despite high compliance with tamoxifen and prednisone therapy. She was admitted for her pain management and her dose of prednisone was increased and she was subsequently discharged home with improvement of her symptoms. Her tamoxifen was switched to mycophenolate on her follow-up visit with gastrointestinal clinic, and her disease has remained stable for the past 2 months. Our case report discusses in-depth the literature on MP and its management. We also detail the steps in management of a rare case of recurrent acute exacerbations of MP despite the patient being on immunosuppressive therapy.